2009
DOI: 10.1111/j.1600-0854.2009.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Calsyntenins Mediate TGN Exit of APP in a Kinesin‐1‐Dependent Manner

Abstract: Kinesin motors are required for the export of membranous cargo from the trans-Golgi network (TGN), yet information about how kinesins are recruited to forming transport intermediates is sparse. Here we show that the Kinesin-1 docking protein calsyntenin-1 localizes to the TGN in vivo and directly and specifically recruits Kinesin-1 to Golgi/TGN membranes as well as to dynamic post-Golgi carriers. Overexpression of various calsyntenin chimeras and kinesin light chain 1 (KLC1) at high levels caused the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 51 publications
(78 reference statements)
8
58
0
Order By: Relevance
“…Calsyntenin-1 is a neuronal transmembrane protein transported to axons in vesicular carriers in a kinesin 1-dependent manner (Konecna et al, 2006;Ludwig et al, 2009). Strikingly, by using the same subcellular fraction method that we use in the present study, Ludwig et al (2009) showed that calsyntenin-1 concentrates in the subcellular vesicle fractions V0 and V1, where we found Ax-NMNAT1 and Wld S mostly present. Although we show that Ax-NMNAT1 does not colocalize with calsyntenin-1, and p38 SNPH, we cannot exclude a possible colocalization with other vesicles of similar size.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Calsyntenin-1 is a neuronal transmembrane protein transported to axons in vesicular carriers in a kinesin 1-dependent manner (Konecna et al, 2006;Ludwig et al, 2009). Strikingly, by using the same subcellular fraction method that we use in the present study, Ludwig et al (2009) showed that calsyntenin-1 concentrates in the subcellular vesicle fractions V0 and V1, where we found Ax-NMNAT1 and Wld S mostly present. Although we show that Ax-NMNAT1 does not colocalize with calsyntenin-1, and p38 SNPH, we cannot exclude a possible colocalization with other vesicles of similar size.…”
Section: Discussionsupporting
confidence: 61%
“…The exit of neurexin from the ER/Golgi and its trafficking to synapses in vesicles depends on its C-terminal sequence, where the domain for interaction with Mint1 resides (Fairless et al, 2008). Although a direct interaction between APP and kinesin is controversial (Kamal et al, 2001;Lazarov et al, 2005), the exit of vesicles containing APP from the trans-Golgi-network is mediated by calsyntenin-1 (Ludwig et al, 2009). Calsyntenin-1 is a neuronal transmembrane protein transported to axons in vesicular carriers in a kinesin 1-dependent manner (Konecna et al, 2006;Ludwig et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calsyntenin-1 is widely expressed but is particularly abundant in the nervous system, where it is present in most neuronal subtypes (Hintsch et al, 2002). As a direct binding partner for KLC1, calsyntenin-1 has been implicated in the transport of a subset of vesicles and especially vesicles undergoing transport through axons of neurons (Araki et al, 2007;Konecna et al, 2006;Ludwig et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Alc␣/ calsyntenin-1 is also subject to intracellular trafficking and metabolism and participates in neural functions, similar to APP (4, 9 -11). Calsyntenins have also been reported to mediate exit of APP from the TGN (12).…”
Section: Alcadein (Alc)mentioning
confidence: 99%